Environmental affected mechanical performance of additively manufactured carbon fiber–reinforced plastic composites. (March 2022) - Adeniran, Olusanmi; Cong, Weilong; Bediako, Eric; Adu, Sunday Peter
Due to their attractive strength-to-weight ratios, stiffness-to-weight ratios, thermal expansion, corrosion resistance, and vibration resistance properties, carbon fiber reinforced plastic (CFRP) composites have been widely used in applications ranging from aerospace to sporting goods. Considering some of the advantages of additive manufacturing (AM) over traditional subtractive methods, AM is being used to fabricate CFRP composites. For the fabrication method, several investigations have been conducted on materials and processing effects on the mechanical performance of the composites. However, no studies have investigated the effects of environmental conditions on mechanical performance. This study reports the environmental (temperature and relative humidity) affected mechanical performance of AM fabricated CFRP composites exposed to three different environmental conditions: warm–wet, warm–dry, and cold–dry, compared to samples tested immediately after fabrication under normal ambient conditions. The result was that the warm temperatures have insignificant effects on the mechanical performance of the composites, while near-zero degree cold temperatures have significant effects after the 96 h and 250 h short-term exposure periods. The result also showed the temperature to have more significant effects on mechanical properties than relative humidity. Under the warm conditions, the dry humidity resulted in a slight increase in material mechanical properties over the nominal ambient condition, while the wet humidity showed an insignificant reduction in material mechanical properties.